2010
DOI: 10.1016/j.bbmt.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Recipient B Cells Are Not Required for Graft-Versus-Host Disease Induction

Abstract: Recipient antigen presenting cells (APCs) are required for CD8-mediated GVHD and have an important and nonredundant role in CD4-mediated GVHD in mouse MHC-matched allogeneic bone marrow transplantation (alloBMT). However, the precise roles of specific recipient APCs — dendritic cells, macrophages, and B cells — are not well defined. If recipient B cells are important APCs they could be depleted with Rituximab, an anti-CD20 monoclonal antibody. On the other hand, B cells can downregulate T cell responses and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Although a previous study indicated that host B cells suppress GVHD, 8 CD19 expression in recipients did not alter the course or severity of Scl-cGVHD (Figure 2). This study demonstrates, for the first time, that Bregs play a critical suppressive role in immune-mediated fibrotic diseases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although a previous study indicated that host B cells suppress GVHD, 8 CD19 expression in recipients did not alter the course or severity of Scl-cGVHD (Figure 2). This study demonstrates, for the first time, that Bregs play a critical suppressive role in immune-mediated fibrotic diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Donor T cells have classically been considered the main effector cells, although recent studies have suggested that B cells also play fundamental roles in GVHD. [5][6][7][8] Circulating autoantibodies are frequently detected in cGVHD patients. 9 Their direct pathogenicity remains unclear, although a recent study has demonstrated that pathogenic antibody production from germinal centers plays a causal role in development of cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Because host hematopoietic-derived APCs can also negatively regulate GVH responses, 37,38 our data indicate that strategies that promote the regulatory APC subsets [39][40][41][42] might be more effective than elimination of hematopoietic-derived activating APC subsets. 28,[43][44][45] Importantly, our data indicate that regulating the process of Ag presentation, rather than targeting any specific host hematopoietic-derived cellular subsets that are capable of activating alloreactive donor T cells, might be a more desirable strategy for mitigating GVHD. …”
Section: Discussionmentioning
confidence: 99%
“…The BST2 hybridoma(27) was a gift from Marco Colonna (Washington University School of Medicine, MO) and was lab-prepared. Anti-mouse CD20 (an IgG2aκ derivative of clone 18B12(28)) was provided by Marilyn Kehry (Biogen/IDEC, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%